CRISPR/Cas9-mediated glycolate oxidase disruption is an efficacious and safe treatment for primary hyperoxaluria type I. Issue 1 (December 2018) - Zabaleta, Nerea; Barberia, Miren; Martin-Higueras, Cristina; Zapata-Linares, Natalia; Betancor, Isabel; Rodriguez, Saray; Martinez-Turrillas, Rebeca; Torella, Laura; Vales, Africa; Olagüe, Cristina; Vilas-Zornoza, Amaia; Castro-Labrador, Laura; et al.
Abstract CRISPR/Cas9 technology offers novel approaches for the development of new therapies for many unmet clinical needs, including a significant number of inherited monogenic diseases. However, in vivo correction of disease-causing genes is still inefficient, especially for those diseases without selective advantage for corrected cells. We reasoned that substrate reduction therapies (SRT) targeting non-essential enzymes could provide an attractive alternative. Here we evaluate the therapeutic efficacy of an in vivo CRISPR/Cas9-mediated SRT to treat primary hyperoxaluria type I (PH1), a rare inborn dysfunction in glyoxylate metabolism that results in excessive hepatic oxalate production causing end-stage renal disease. A single systemic administration of an AAV8-CRISPR/Cas9 vector targeting glycolate oxidase, prevents oxalate overproduction and kidney damage, with no signs of toxicity inAgxt1 −/− mice. Our results reveal that CRISPR/Cas9-mediated SRT represents a promising therapeutic option for PH1 that can be potentially applied to other metabolic diseases caused by the accumulation of toxic metabolites. Substrate reduction therapies (SRT) are a promising therapeutic approach for monogenic inherited metabolic diseases. Here the authors evaluate the therapeutic potential of an in vivo CRISPR/Cas9-mediated SRT to treat primary hyperoxaluria type I and demonstrate its safety and efficacy.